The Application Of The Role Of Islamic Religious Education Teachers In Shaping The Character Of Students Based On Islamic Teachings At Smp Negeri 3 Colomadu - Gigih Adi Kurniawaan; Zainal Abidin (Jurnal Indonesia Sosial Teknologi, 2023)
This research aims to: 1) Find out the character of students at SMP Negeri 3 Colomadu; 2) Knowing and analyzing the role of PAI teachers in shaping student character at SMP Negeri 3 Colomadu; 3) Find out what factors support and hinder the formation of student character at SMP Negeri 3 Colomadu. This research was carried out in August-September 2023 at SMP Negeri 3 Colomadu. The research method used is a qualitative method. The results found in this research are as follows: 1) The character of students at SMP Negeri 3 Colomadu in terms of religion and responsibility is said to be good. Various efforts have been made by the school to overcome problems in the formation of students' religious character and responsibility, including by getting into the habit of Dhuha, Muhadarah and Friday prayers regularly held every Friday; 2) The role of PAI teachers in improving the character of students at SMP Negeri 3 Colomadu, including: educator, tutor, leader, mentor, advisor or motivator, evaluator, coordinator, and role model; 3) Supporting factors in forming the religious character and responsibility of students at SMP Negeri 3 Colomadu are influenced by: the curriculum content standards used, the leadership of the school principal, the role of the teacher, the commitment of the entire school community, and the role of parents in the school program. Meanwhile, the inhibiting factors are: lack of concern from some parents and teachers, lack of parental knowledge about character education, school environment that is less supportive, and lack of awareness among students.